Volumetric modulated Arc Therapy versus 3D conformal radiotherapy in the treatment of locally advanced cervical cancer. A single institution, comparative dosimetric study - Bhagaloo, Visham (Division of Radiology, 2021)
Background: External Beam Radiotherapy is essential in the management of locally advanced cervical cancer (LACC). Generally, VMAT is thought to achieve higher conformity to the Planned Target Volume (PTV) and better sparing of organs at risk (OAR) when compared to 3D-CRT. This study focused on these principles as it applied to treatment and potential toxicity in the management of LACC. Aim: To compare dosimetric parameters between VMAT and 3D-CRT in the management of LACC. Setting: The study analysed patients treated at Groote Schuur Hospital between May and December 2017. Method: A non-randomized comparative retrospective study. EBRT plans for 3D-CRT and VMAT were generated and data on treatment parameters for PTV D50%, Dmax, Dmean, Conformity Index (CI), Homogeneity Index, Treated Volume (TV), Irradiated Volume (IV) and OAR constraints; femoral heads, bladder, bowel bag, rectum and bone marrow were collected. Results: Of the 45 patients assessed, VMAT showed significantly lower treatment parameter values for CI (1.09 vs 1.49; p< .001) whereas, 3D-CRT showed lower Dmax (48.1Gy vs 49.2Gy; p< .001) and rectum (88.5% vs 96%). A reduced 3D-CRT dose was noted for bladder Dmax (47.4Gy vs 48.3Gy; p< .001). Conclusion: VMAT offered a superior dosimetric option, with better OAR dose sparing and optimal tumour dosimetry.